Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content: 1. The reality of the application of leaders and supervisors in public and private primary schools in Jeddah to indicators of learning outcomes in the light of the supervisory performance leadership system in Saudi schools Mrs. Sulafah Salah Bajabir , Prof. Najat Mohammed Saeed Alsaigh 2. The Interactive Role of Emotional Intelligence in the Relationship between Positive Leadership Behaviors and Job Involvement: An Analytical Study of the Opinions of Academic Leaders in Saudi Universities Co-Prof. Tawfeeq Zayed Mohammad Alregeb 3. The effect of teaching using electronic visual notation in developing the skills of jurisprudence of inheritance among secondary school students Mrs. Huda Muhsiny Altalhi , Prof. Abdullah Mohamad Ayed Al Tameem 4. Obstacles to using authentic evaluation strategies in teaching natural sciences from the point of view of science teachers in the both primary and intermediate stages in the city of Makkah Al-Mukarramah Mr. Mukhlid Saad Al-Otaibi 5. Mind- wandering and its Relationship to Academic Engagement among Umm Al- Qura University Students Mrs. Taghreed Daefallah Al- Huthale , Co- Prof. Nawar Mohammad Saad Al- Harbi 6. Emotional Creativity and its relationship to Cognitive Representation and Locus of Control among Talented and Untalented High School female students in Makkah Al-Mukarramah Mrs. Haneen Ibrahim Alsubhi 7. Psychological burnout and its relationship to family adjustment among mothers of children with autism in centers for people with special needs in Khartoum Mrs. Sarah Mohamed Ahmed Al- Kashef